Cross-border cooperation between securities regulators - Silvers, Roger (Journal of Accounting and Economics, 2020)
The events of September 11, 2001, prompted sweeping cross-border coordination efforts for securities regulators around the globe. After 9/11, the International Organization of Securities Commissions (IOSCO) forged a nonbinding arrangement—the Multilateral Memorandum of Understanding Concerning Consultation and Cooperation and the Exchange of Information (MMoU)—that standardized the protocol for information sharing among participating securities regulators. Because regulators from different countries entered the MMoU at different times, their enlistments created a set of staggered shocks. I use these shocks to show that the resulting cross-border cooperation (a) increases cross-border enforcement and (b) reduces the cost of liquidity provision in the capital markets of participating countries. These results support the conclusion that the MMoU helps fill gaps in cross-border regulation that historically exposed investors to information asymmetry, agency costs, and expropriation risks.